Cryphonectria hypovirus 1 (CHV‐1) survey reveals low occurrence and diversity of subtypes in NE Spain. Issue 1 (22nd July 2014) - Castaño, C.; Bassie, L.; Oliach, D.; Gómez, M.; Medina, V.; Liu, B.; Colinas, C.; Balci, Y.
Summary Cryphonectria parasitica (Murrill.) Barr is a necrotrophic fungus that affects European chestnut populations. In Catalonia (NE Spain), this fungus is widely spread affecting chestnut stands. In addition to vegetative compatibility (VC) types of the fungus, knowledge of the Cryphonectria hypovirus (CHV) occurrence is important to implement a biocontrol programme. We confirmed the presence of hypoviruses in several chestnut subpopulations of Catalonia, and we determined the VC types of CHV‐infected isolates. We also studied the nucleotide sequences of these hypoviruses from a variable region located in the hypovirus ORF‐A. Our results show a low occurrence of hypoviruses throughout C. parasitica populations in Catalonia, except for a few localized stands. From 312 sampled cankers, we obtained 179 white, pale orange or rickety isolates. In 35 of them, we detected CHV‐1. Infected isolates belonged to 5 of the 7 sampled subpopulations. We found 12 CHV‐1 haplotypes, based on the nucleotide sequence analysis. Most of the hypoviruses have the same nucleotide sequence or show high homology at nucleotide level with isolates previously included in CHV‐1 subtype‐I. However, we found that 3 haplotypes share at least 97% of their ORF‐A nucleotide sequence with CHV‐1 subtype‐E. Phylogenetic analysis grouped these 3 isolates in a different cluster than the other hypoviruses. These results suggest that multiple introductions of CHV‐1 have occurred recently in Catalonia. Dominant VC types of hypovirus‐infected isolates are EU‐1, EU‐2 and EU‐5, which are similar to those previously reported in this region.